(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the realm of effective online learning methods designed to facilitate the acquisition of foreign languages. The discussion encompasses a diverse array of digital tools and platforms, emphasizing their transformative impact on language education. The highlighted methods include Interactive Communication Platforms, which enable real-time engagement with native speakers, creating dynamic and culturally rich language learning experiences.